Electrochromic Properties of Sol-gel Deposited Ti-doped Vanadium Oxide Film - Özer, Nilgün; Sabuncu, Sevsen (ELSEVIER SCIENCE SA, PO BOX 564, 1001 LAUSANNE, SWITZERLAND, 1999)
Titanium-doped vanadium pentoxide, (100 - x)V2O5.xTiO(2) films with compositions ranging from 0 to 20 mole % titanium were prepared by using sol-gel dip coating techniques. Highly transparent (100 - x)V2O5.xTiO(2) films With properties superior to vanadium oxide were formed. The coating solutions were prepared by reacting vanadium tri-isopropoxide oxide and titanium tetra-isopropoxide as precursors and anhydrous isopropanol as solvent. The films were formed on transparent conducting substrates by a dip coating technique and heat treated at 300 degrees C for 1 h. The films were characterized by cyclic voltammetry, optical spectroscopy, scanning electron microscopy +/- SEM, and X-ray diffractometer (XRD). XRD results show that the films heat treated at temperatures below 400 degrees C were amorphous. The electrochemical lithium insertion shows that (100 - x)V2O5.xTiO(2) films exhibited good recharge ability of Li+/e(-) insertion/extraction process. Spectroelectrochemical measurements from 300 to 800 nm show that (100 - x)V2O5;O-5.xTiO(2) films exhibit weak cathodic coloration in the near uv and weak anodic coloration from 500 to 800 nm. It was observed that the addition of titanium resulted in marked improvement in the electrochromic behavior. This was especially seen for vanadium pentoxide doped with 5 mole % titanium. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: Optical Coatings; Optical Spectroscopy; Vanadium Oxide; Electrochemistry; Optik Kaplamalar; Optik Spektroskopi; Vanadyum Oksit; Elektrokimya